Analogical Reasoning in Solving Indirect Problem-Based Area Problems - Nuridah, Eka Rahmah; Amir, Mohammad Faizal (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2023)
This study aims to identify the stages of students' analogical reasoning in solving indirect problems. The type of research used is qualitative with a case study approach. The participants in this study were 25 fifth-grade students who selected research subjects using purposive techniques that represent each analogical reasoning category based on the analogical reasoning test. Data collection techniques used indirect problem tests and interviews. Data analysis techniques included data reduction, presentation, and verification. The results showed that there were two categories of students' analogical reasoning when solving indirect analogy problems: (1) Indirect problem succeeded, students who successfully solve source problems and target problems by using all stages of analogical reasoning, namely representation and mathematical modeling, structuring, mapping, applying, verifying; (2) Indirect problem failed, students who did not successfully solve source problems and target problems by using all stages of analogical reasoning. The results of this study suggest that educators, especially at the elementary level, should explore more deeply the students' ability to solve indirect analogical problems with analogical reasoning.